2023
DOI: 10.1021/jacs.2c12305
|View full text |Cite
|
Sign up to set email alerts
|

How Can Static and Oscillating Electric Fields Serve in Decomposing Alzheimer’s and Other Senile Plaques?

Abstract: Alzheimer’s disease is one of the most common neurodegenerative conditions, which are ascribed to extracellular accumulation of β-amyloid peptides into plaques. This phenomenon seems to typify other related neurodegenerative diseases. The present study uses classical molecular-dynamics simulations to decipher the aggregation–disintegration behavior of β-amyloid peptide plaques in the presence of static and oscillating oriented external electric fields (OEEFs). A long-term disintegration of such plaques is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 96 publications
0
14
2
Order By: Relevance
“…Previous studies have shown that the application of an external electric field would prevent the formation of hairpin structure of the apoC-II (60–70) peptide . Furthermore, in a simulation study of oligomers of the heptapeptide segment Aβ(16–22) degradation of the secondary structure content was observed upon application of oscillating electric fields (of strengths 100 mV/nm at 0.1 GHz and 200 mV/nm at 1 GHz) . There are major differences between the work by Kalita et al and our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Previous studies have shown that the application of an external electric field would prevent the formation of hairpin structure of the apoC-II (60–70) peptide . Furthermore, in a simulation study of oligomers of the heptapeptide segment Aβ(16–22) degradation of the secondary structure content was observed upon application of oscillating electric fields (of strengths 100 mV/nm at 0.1 GHz and 200 mV/nm at 1 GHz) . There are major differences between the work by Kalita et al and our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Information regarding the inhibition process will further help to develop better medication for other neurodegenerative diseases. 101,[125][126][127][128][129] Fig. 15 Schematic presentation of the formation of nano-aggregates in the presence of metal ions with a higher charge-to-radius ratio resulted in the enhancement of the blue intrinsic fluorescence property.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding the inhibition process will further help to develop better medication for other neurodegenerative diseases. 101,125–129…”
Section: Discussionmentioning
confidence: 99%
“…Ever since these seminal contributions, the interest in the effects of (local) electric fields, both those exerted by the protein matrix in enzymes, as well as by molecular constituents in other catalytic systems and set-ups, has soared. A virtuous cycle of theoretical predictions being confirmed by ingenious experiments, which in their turn sparked new theoretical insights, has been triggered and is resulting in exciting advances across the field. Of particular interest in recent years is the effect of electrostatics on the function of the water, a pivotal solvent for biological systems. For example, a theoretical study by Cassone showed that the presence of an electric field causes delocalization of the electron density of a water molecule, which lowers the ionization threshold resulting in altered kinetics of proton transfer .…”
Section: Introductionmentioning
confidence: 99%